Navigating ethical dilemmas in complementary and alternative medicine: a narrative review - Mohammad Sadegh Adel Mehraban; Asieh Mosallanejad; Mehdi Mohammadi; Ozra Tabatabaei Malazy; Bagher Larijani (Journal of Medical Ethics and History of Medicine, 2024)
Complementary and alternative medicine (CAM) is a rapidly growing industry, with millions worldwide seeking these treatments for various ailments. While many CAM therapies have shown promise in improving health outcomes, there are also ethical challenges associated with them. In this article, we explore some of the most pressing ethical issues in CAM, including informed consent, justice in accessibility, and evidence-based therapies. This survey provides a comprehensive overview of the ethical issues in CAM and offers practical guidance for health-care providers navigating these complex issues. By understanding the ethical dilemmas in CAM, health-care providers can offer their patients safe and effective care while maintaining their professional and ethical obligations.